DAMPAK MEDIA SOSIAL TERHADAP KESEHATAN MENTAL GEN Z - Kartika Dewi; Nasywa Az Zahra Sopyan; Nur Agustina Setiani Putri; Rama Wijaya Abdul Rozak (Cahaya Ilmu Bangsa Institute, 2025)
Generation Z is increasingly using social media to communicate, share experiences and connect with others. However, there are concerns that excessive or unhealthy use of social media can negatively impact mental health. This study aims to find out how social media impacts mental health. This study uses interview techniques, 3 Generation Z people were selected as samples to measure the level of social media use and how it can impact their mental health. based on the research conducted, social media is very impactful on the mental health of Gen Z both positively and negatively. the negatives are anxiety when unable to access social media, difficulty focusing, stress, insecurity which can trigger disruption of mental health. as for the positive side is positive interaction on social media.